2008
DOI: 10.1158/0008-5472.can-08-1488
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Prostate Cancer Nodal and Systemic Metastasis by Blockade of the Lymphangiogenic Axis

Abstract: Lymph node involvement denotes a poor outcome for patients with prostate cancer. Our group, along with others, has shown that initial tumor cell dissemination to regional lymph nodes via lymphatics also promotes systemic metastasis in mouse models. The aim of this study was to investigate the efficacy of suppressive therapies targeting either the angiogenic or lymphangiogenic axis in inhibiting regional lymph node and systemic metastasis in subcutaneous and orthotopic prostate tumor xenografts. Both androgen-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 44 publications
9
116
2
1
Order By: Relevance
“…76,78,86 Use of different prostate cancer models has shown a VEGF-C dependency of intratumoral lymphatic vessels. 75,89 Furthermore, in a VEGF-C-expressing prostate cancer model (PC3), ablation of intratumoral vessels by a VEGF-C and VEGF-D binding decoy receptor did not decrease metastasis, suggesting that peritumoral lymphatic vessels were sufficient for tumor metastasis in this model. 89 Some imaging studies have shown that intratumorally injected tracers may be deposited in tumors instead of being cleared by lymphatic drainage.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 91%
See 3 more Smart Citations
“…76,78,86 Use of different prostate cancer models has shown a VEGF-C dependency of intratumoral lymphatic vessels. 75,89 Furthermore, in a VEGF-C-expressing prostate cancer model (PC3), ablation of intratumoral vessels by a VEGF-C and VEGF-D binding decoy receptor did not decrease metastasis, suggesting that peritumoral lymphatic vessels were sufficient for tumor metastasis in this model. 89 Some imaging studies have shown that intratumorally injected tracers may be deposited in tumors instead of being cleared by lymphatic drainage.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 91%
“…74 VEGF-C-induced dilation of collecting vessels around tumors may allow the entry of clusters of metastatic tumor cells. 78,79 Even tumors that rarely metastasize through the lymphatic vessels, for example, the fibrosarcoma T241 and the prostate cancer cell line LAPC9, have been observed to do so when manipulated to overexpress VEGF-C. 20,65,75 Although VEGF-D overexpression in mouse models resulted in increased lymphangiogenesis and metastasis, 72,80 correlation between VEGF-D expression levels and lymph node metastasis in patients has been found only in less than half of the studies. 73 VEGF-D may play a limited role in tumor lymphangiogenesis, as low expression levels have been found in most patient-derived cell lines and Figure 2.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF isoforms exhibit distinct receptor affinities and activate the intracellular receptor tyrosine kinase signaling cascade. The VEGFs and their receptors also play a role in PCa lymphangiogenesis (Wong et al 2005, Burton et al 2008. In the present review, we focus on the regulation and function of VEGFA (also referred to as simply VEGF) in angiogenesis.…”
Section: Transcriptional Regulation Of Pro-angiogenesis Pathways In Pcamentioning
confidence: 99%